The problems to access state services for blind and visually impaired persons and the libraries role in their solution - S. S. Battalova; M. S. Petrova (Библиосфера, 2018)
Access to public services, both online and in situ (through multifunctional public service centers) is a key element in developing e-government and provision of equal opportunities for all groups of citizens. Saint Petersburg State Library for the Blind and Visually Impaired Persons in cooperation with the Saint Petersburg Regional Organization of the All-Russian Society of the Blind carried on a research to determine the target audience needs to assess the state and identify problems of access to public services for people with visual impairments. The study main objective was to evaluate principles and methods of obtaining public services by people with visual problems, reveal main problems in obtaining services and determine ways to solve them. The results obtained during the research show both a high degree of demand in public services for the target audience and a number of problems in obtaining them both online and in multifunctional service centers. In this regard, the library can take over consultative functions to provide comprehensive professional information support to its users in the area of public services.